Evolution, expression, and substrate specificities of aldehyde oxidase enzymes in eukaryotes - Terao, Mineko (2022)
This work was supported by Deutsche Forschungsgemeinschaft Grant Le1171/8-3 (to S. L.). FCT-MCTES, research unit UCIBIO (UID/Multi/04378/2019). project PTDC/BBB-BEP/1185/2014 (to M. J. R.). Fondazione Italo Monzino and the Associazione per la Ricerca sul Cancro (AIRC) (to E. G.).